2017
DOI: 10.1111/are.13415
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait locus mapping of growth‐related traits in inter‐specific F 1 hybrid grouper ( Epinephelus fuscoguttatus  ×  E. lanceolatus ) in a tropical climate

Abstract: Growth‐related traits are the main target of genetic breeding programmes in grouper aquaculture. We constructed genetic linkage maps for tiger grouper (Epinephelus fuscoguttatus) and giant grouper (E. lanceolatus) using 399 simple sequence repeat markers and performed a quantitative trait locus (QTL) analysis to identify the genomic regions responsible for growth‐related traits in F1 hybrid grouper (E. fuscoguttatus × E. lanceolatus). The tiger grouper (female) linkage map contained 330 markers assigned to 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Studies on other teleost species, including stickleback, have also reported detailed empirical evidence of sexually dimorphic recombination rates, calculating female:male recombination ratios of linkage map lengths to be 1.64 (Sardell et al 2018). Future work should aim to compare and contrast the recombination landscape of whitefish to the detailed sexually dimorphic recombination patterns observed in drosophila, mice, deer and various fish species (Dunn 1920; Sakamoto et al 2000; Lenormand and Dutheil 2005; Johnston et al 2017; Kubota et al 2017; Sardell et al 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on other teleost species, including stickleback, have also reported detailed empirical evidence of sexually dimorphic recombination rates, calculating female:male recombination ratios of linkage map lengths to be 1.64 (Sardell et al 2018). Future work should aim to compare and contrast the recombination landscape of whitefish to the detailed sexually dimorphic recombination patterns observed in drosophila, mice, deer and various fish species (Dunn 1920; Sakamoto et al 2000; Lenormand and Dutheil 2005; Johnston et al 2017; Kubota et al 2017; Sardell et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Linkage maps have become an essential tool in investigating evolution in non-model systems, providing information about the relative locations of markers along the genome and assisting in the assembly of new de novo genomes (Ellegren 2013; da Fonseca et al 2016; Sutherland et al 2016; Kubota et al 2017; Sun et al 2017; Zhigunov et al 2017; Matz 2018). Many non-model organisms have specific ecological and evolutionary characteristics which make them particularly interesting for asking targeted evolutionary questions (Matz 2018).…”
mentioning
confidence: 99%